2023
DOI: 10.47405/mjssh.v8i2.2138
|View full text |Cite
|
Sign up to set email alerts
|

Perubahan Iklim: Pengetahuan Pedagogi Isi Kandungan Guru Sains di Sekolah Menengah

Abstract: Kajian ini dijalankan bertujuan untuk meneroka pengetahuan pedagogi isi kandungan (PPIK) guru sains sekolah menengah bagi topik perubahan iklim. Untuk itu, kajian kuantitatif digunakan bagi tujuan tersebut. Pemilihan sampel kajian adalah dari kalangan guru sains sekolah menengah harian di sekitar Kuala Lumpur. Instrumen yang digunakan dalam kajian ini adalah soal selidik dengan menggunakan skala Likert lima mata. Instrumen ini terdiri daripada empat bahagian utama iaitu bahagian demografi (3 item), bahagian pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The teacher may need help explaining complex concepts and theories to the students, leading to confusion and poor learning outcomes. In a study conducted by Masingan & Sharif (2019), it was found that teachers who were not from a technical background lacked a comprehensive understanding of the objectives, goals, and focus of the D&T subject, which led to difficulties in mastering its content, especially in the field of electronic design.…”
Section: Resultsmentioning
confidence: 99%
“…The teacher may need help explaining complex concepts and theories to the students, leading to confusion and poor learning outcomes. In a study conducted by Masingan & Sharif (2019), it was found that teachers who were not from a technical background lacked a comprehensive understanding of the objectives, goals, and focus of the D&T subject, which led to difficulties in mastering its content, especially in the field of electronic design.…”
Section: Resultsmentioning
confidence: 99%
“…In this scenario, concrete learning may be linked with a learning design that encourages children to tinker with what they observe. Learning through visual activities aided by technology can help students establish a concept of the content being studied (Akhwani & Rahayu, 2021;Augustine, R. B., & Mohamed, 2023). However, visual activities in learning devices or teaching modules, such as reading activities without the use of technology, become a way of learning to recall concepts.…”
Section: Discussionmentioning
confidence: 99%